2013
DOI: 10.1007/s00280-013-2332-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced efficacy of postoperative adjuvant chemotherapy in advanced gastric cancer: results from a phase 3 randomized trial (AMC0101)

Abstract: The efficacy of adjuvant Mf was significantly improved by the additional therapeutic strategies of iceMFP. Considering negative results of AMC0201, these suggest that early initiation of chemotherapy and/or intraperitoneal cisplatin played a distinct role in the improved efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…An additional concern worthy of exploration is whether toxicity from IP chemotherapy administration caused patients to not receive other planned adjuvants, such as post‐operative systemic chemotherapy. Seven studies identified here gave details on administration of post‐operative chemotherapy, but only three (Kang et al, Miyashiro et al, and Atiq et al,) provided information regarding whether surgical morbidity had an impact of the receipt of subsequent systemic chemotherapy . Two of these three studies were RCTs, but only one, Kang et al, gave adjuvant systemic chemotherapy to both arms (albeit slightly different regimens).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional concern worthy of exploration is whether toxicity from IP chemotherapy administration caused patients to not receive other planned adjuvants, such as post‐operative systemic chemotherapy. Seven studies identified here gave details on administration of post‐operative chemotherapy, but only three (Kang et al, Miyashiro et al, and Atiq et al,) provided information regarding whether surgical morbidity had an impact of the receipt of subsequent systemic chemotherapy . Two of these three studies were RCTs, but only one, Kang et al, gave adjuvant systemic chemotherapy to both arms (albeit slightly different regimens).…”
Section: Resultsmentioning
confidence: 99%
“…The largest randomized trial by Kang et al was also the most recent study, randomizing 521 patients with stages II–III gastric cancer to normothermic IP chemotherapy versus surgery alone, with all patients receiving systemic chemotherapy . The resulting 5‐year overall survival of 59% versus 50% in favor of the IP chemotherapy group was statistically significant ( P = 0.006) . Furthermore, the most recent RCT using heated IP chemotherapy by Yonemura et al also reported improved outcomes with a 5‐year OS of 61% for surgery plus HIPEC versus 42% for surgery alone .…”
Section: Discussionmentioning
confidence: 99%
“…For the five included studies, three 14 15 16 studies were rated as low risk in “randomization sequence”. The randomization was generated by using a random number table 16 or permutation block randomization 15 . Patients were randomly assigned to accepted interventions in two studies.…”
Section: Resultsmentioning
confidence: 99%
“…Two 14 16 studies were rated as low and high risk in allocation concealment respectively, mainly because the former used a sealed envelope while the latter was an open-label study. Four studies 14 15 16 17 were rated as unclear risk in “blinding of participants and outcome assessor” and one was rated as high risk because of the open label design. Four studies 13 14 17 were rated as low risk in “incomplete outcome data” and one 16 was rated as unclear.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation